Portraits - Fredericks, Gaireyah (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Die portfolio bestaan yt reflections op my writing process during die course, my reading, my poetics essay en vier boek resensies.
Keywords: Kaaps; Creative writing (Higher education) -- South Africa; Diaries -- Authorship; Books Reviews; Afrikaans essays 21st century; Short stories, Afrikaans 21st century